Estimation of Blockage Effects of Complex Structures on the Performance of the Spacecraft Reflector Antennas by a Hybrid PO/NF-FF Method - Bahadori, Keyvan; Rahmat-Samii, Yahya (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A hybrid (PO/NF-FF) method is presented in this paper for estimating the blockage effects of complex structures on the performance of the spacecraft mounted reflector antennas. The method estimates the blockage effect based on null-field hypothesis. The main advantage of this method is its ease of implementation for different obstacle geometries. The accuracy and functionality of the method is demonstrated by comparing the results of this method with other methods such as Method of Moments (MoM) and Direct (PO). An alternative definition of beam efficiency is adopted when the radiated power is available only in the forward radiation region. As a case study, the method is used to evaluate the effects of side panels on the performance of a reflector antenna operating at K band. A new parameter is also defined to represent the effects of absorbed power by panels. This parameter may be used to estimate the contribution of absorbed power in increasing system noise temperature.